Market Conditions in Long-Run IPO Performance in Junior Markets - Vachekrilas, Kasidid; Ousawat, Thitapon; Sangbua, Rinrada (Journal of Posthumanism, 2025)
The objective of this research was to investigate the ‘hot market’ hypothesis in the long-run performance of initial public offerings on Thailand’s junior stock market, the Market for Alternative Investments (mai). A long run event study methodology was used, with periods of six, twelve, twenty-four and thirty-six months from the initial public offering selected for analysis. Predictor variables included trading volume, initial public offering frequency, and systemic crisis (2020-2022). Data was collected for 151 firms which issued an initial public offering between 2012 and 2023. The findings showed that trading volume was not a significant predictor of performance. However, initial public offering frequency negatively predicted performance, while systemic crisis positively predicted performance. The implication of this is that firms that enter the market during ‘hot’ periods may be systematically overpriced and as a result may underperform later.